Implementation of the installation monitoring plan in an energy company - Cieślak, Robert (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2023)
The work presents five stages of implementation of the assembly platform in an energy company. It focuses on indicating the adaptation of the assembly platform for the final product, which are low, medium and high voltage switchboards in the energy company. The first two chapters present the definition and application of the assembly platform. The next chapter deals with the research carried out on the introduction of the assembly platform to the energy company. The work ends with a summary and conclusions. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)